MAKNA تحرير /TAHRIR/ DALAM TEKS BERITA MEDIA ARAB DARING AL-JAZEERA (KAJIAN SEMANTIK) - Resty Syahrotul Aini; Mardjoko Idris (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
Media is a channel for information that is still used today. There are many issues circulating with various media reporting them. One of the issues that is always widely discussed is the Palestinian-Israeli conflict which is heating up again at the moment. The discourse on Palestinian liberation has always been a hot topic. This gives rise to the emergence of lexemes or language units that are appropriate to the Palestinian-Israeli conflict, such as the word tahrir. This research aims to explain the lexical and contextual meaning in the online Arabic media Al-Jazeera which highlights the Palestinian-Israeli conflict. This research is descriptive qualitative research. The data source comes from Al-Jazeera media with the help of AntConc and LancBox software in collecting data. The research results showed that lexical meaning was found by 64% and contextual meaning was found by 36%. Al-Jazeera reporting tends to use the word tahrir in its lexical meaning as liberation. Meanwhile, using the word al-tahrir has a contextual meaning that is oriented towards the name of the liberation organization in Palestine.